Progression of Type 1 Diabetes: Circulating MicroRNA Expression Profiles Changes from Preclinical to Overt Disease. (19th July 2022) - Santos, Aritania Sousa; Ferreira, Ludmila Rodrigues Pinto; da Silva, Amanda Cabral; Alves, Laís Isidoro; Damasceno, Jullian Gabriel; Kulikowski, Leslie; Cunha-Neto, Edecio; da Silva, Maria Elizabeth Rossi
Abstract : Aims/Hypothesis . The role of microRNAs (miRNAs) in type 1 diabetes (T1D) pathogenesis and progression has been described but remains elusive. Objectives . To evaluate the potential biological involvement of miRNA expression in the immune response and beta cell function in T1D. Methods. We screened 377 serum miRNAs of 110 subjects divided into four groups: healthy individuals (control group) and patients at different stages of T1D progression, from the initial immunological manifestation presenting islet autoantibodies (AbP group) until partial and strong beta cell damage in the recent (recent T1D group) and long-term T1D, with 2 to 5 years of disease (T1D 2-5y group). Results. The results revealed 69 differentially expressed miRNAs (DEMs) in relation to controls. Several miRNAs were correlated with islet autoantibodies (IA2A, GADA, and Znt8A), age, and C-peptide levels, mainly from AbP, and recent T1D groups pointing these miRNAs as relevant to T1D pathogenesis and progression. Several miRNAs were related to metabolic derangements, inflammatory pathways, and several other autoimmune diseases. Pathway analysis of putative DEM targets revealed an enrichment in pathways related to metabolic syndrome, inflammatory response, apoptosis and insulin signaling pathways, metabolic derangements, and decreased immunomodulation. One of the miRNAs' gene targets was DYRK2 (dual-specificity tyrosine-phosphorylation-regulated kinase 2), which is an autoantigen targeted by an antibody in T1D. ROC curve analysis showed hsa-miR-16 and hsa-miR-200a-3p with AUCs greater than for glucose levels, with discriminating power for T1D prediction greater than glucose levels. Conclusions/Interpretation. Our data suggests a potential influence of DEMs on disease progression from the initial autoimmune lesion up to severe beta cell dysfunction and the role of miRNAs hsa-miR-16 and hsa-miR-200a-3p as biomarkers of T1D progression.